Al Munasabah dalam Al Quran - Hakmi Hidayat; Himayatul Maghfiroh; Muhammad Fatih Farhat (Jurnal Kajian Islam dan Sosial Keagamaan, 2024)
This article reviews the concept of Al-Munasabah in the Quran as an important foundation in the study of Ulumul Quran. Al-Munasabah is the study of the relationships and interrelationships between verses and letters in the Quran. Through understanding this concept, readers will be invited to explore its various important aspects, including how Al-Munasabah affects the interpretation and understanding of Quranic verses. The article also discusses the role of Al-Munasabah in strengthening belief in the revelation and miracles of the Quran, and how this knowledge can help in interpreting verses in a more precise and detailed manner. As such, this article provides a deep insight into the importance of understanding the concept of Al-Munasabah in the context of Ulumul Quran studies.